Dream of European Army: Is It a Feasible Objective or Not? - Sevil Şahin; Mustafa Ozan Şahin (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
The European Union’s (EU) defense initiatives have changed over time, reflecting both the pursuit of security and defense goals and the shifting dynamics of European integration. To improve defense cooperation and create a common defense strategy for the EU, several initiatives have been made. The EU’s Common Security and Defense Policy (CSDP), which strives to strengthen its capacity to handle security concerns and preserve stability, has a significant influence on defense-related operations. We have witnessed new security and military efforts from the EU in the first two decades of the 2000s, such as the European Security Strategy, EU’s Global Strategy and Security Compass. 2013 marked a turning point when the USA deployed its new nuclear weapons in Europe. The announcement of the creation of the European army was made on November 13, 2017. Europe should be able to act independently in areas of defense and security rather than merely relying on the US or NATO. Because of these kinds of reservations, desires to pursue more advanced capabilities on their own have been raised.There has been a lot of debate and analysis around the reasons for and against the formation of a European army. Numerous parties have expressed interest in and influence over the notion of a European army. The development of a European army has been heavily debated over the past several years. Why is the idea of a European army so heavily investigated? Is building such an army a realistic goal or not? What are the benefits, drawbacks, and challenges to achieving it? Who is in favor of and against building an army in Europe? These are the primary questions that we attempt to address in this article.